Casos de doenças de chagas nas comunidades ilha do Capim, rios Maracapucú Sagrado e Xingu no município de Abaetetuba-PA - CAVALCANTE, Ewerton Souza (2019)
The present article sought to highlight some reflections on the rates of contamination of chagas disease in three riverside communities in the municipality of Abaetetuba-PA, based on scientific data on chagas disease, a tropical disease that affects thousands of people, especially in the Americas Central and South, is caused by a protozoan known as trypanosoma cruzi, which is transmitted to humans by an insect belonging to the family of triatomids, which contract the parasite in its natural reservoir. There are several other ways that humans can become contaminated with the protozoan T. cruzi, such as blood transfusion, organ transplantation, oral and sexual transmission. The parasite develops in the body of humans causing various complications leading to acute and chronic medical conditions, the first being the initial stage of the disease is easier to be fought, since the second is the chronic phase of the disease causing permanent proliferation of the parasite in the body causing various complications in the nervous, cardiac and digestive system. The diagnosis of the disease can be made from laboratory tests taking into account the specific treatment (eradication of the parasite) and the symptomatic treatment (management of lesions and disorders produced by parasitosis), both of which are important in the treatment of both acute and chronic of Chagas disease. Based on this knowledge, we intend to discuss the presence of Chagas' disease in the Baixo Tocantins region specifically in the Baetetubense region, taking into account the quality of life of these populations, promoting discursions about why several people are contracting the disease and which are the main causes that motivate the appearance of the same in these environments, making surveys, from data in the field of Endemias and field research.